Optimized In vitro propagation and somatic embryogenesis of camu camu (Myrciaria dubia) cultivar Vitahuayo for enhanced commercial production - Adrianzén, Pedro M. (2025)
Background: Myrciaria dubia “camu-camu” a fruit-bearing shrub native to the Amazon, is known for its high vitamin C content. However, variations in vitamin C biosynthesis and accumulation among different cultivars present challenges for commercial production. This study aimed to establish an efficient in vitro regeneration protocol for the Vitahuayo cultivar through callus induction and somatic embryogenesis. Methods: Stem and leaf explants were cultured on Murashige and Skoog (MS) medium supplemented with 24-dichlorophenoxyacetic acid (24-D) and 6-benzylaminopurine (BAP) to induce callus formation. Somatic embryos were induced using Woody Plant Medium (WPM) supplemented with 2,4-D, thidiazuron (TDZ), indole-3-butyric acid (IBA), naphthaleneacetic acid (NAA) and kinetin (KIN). Result: The best results for callogenesis were obtained with 1 mg/L of 24-D and 0.5 mg/L BAP. Somatic embryos were successfully induced with treatments T2 (2,4-D at 3 mg/L, NAA at 20 mg/L and KIN at 15 mg/L) showing 90% efficiency, while T3 (KIN at 0.3 mg/L and BAP at 0.05 mg/L) achieved 57.5% effectiveness. These findings offer great potential for the large-scale propagation of Vitahuayo, the optimization of its commercial production and the standardization of vitamin C biosynthesis.